Societal Change and Values in Arab Communities in Israel: Intergenerational and Rural–Urban Comparisons. (January 2015) - Weinstock, Michael; Ganayiem, Maysam; Igbaryia, Rana; Manago, Adriana M.; Greenfield, Patricia M.
This study tested and extended Greenfield's theory of social change and human development to adolescent development in Arab communities in Israel undergoing rapid social change. The theory views sociodemographic changes—such as contact with an ethnically diverse urban setting and spread of technology—as driving changes in cultural values. In one research design, we compared three generations, high school girls, their mothers, and their grandmothers, in their responses to value-assessment scenarios. In a second research design, we compared girls going to high school in an ethnically diverse city with girls going to school in a village. As predicted by the theory, a t test and ANOVA revealed that both urban life and membership in the youngest generation were significantly related to more individualistic and gender-egalitarian values. Regression analysis and a bootstrapping mediation analysis showed that the mechanism of change in both cases was possession of mobile technologies.